Optimalisasi Potensi Desa Tanjung Saleh dan Sakita dalam Peningkatan Kesadaran Perilaku Hidup Bersih dan Sehat - Jaguna, Fahmi; Sibua , Amrin; Hayun, Subhan; Sabban, Irawati; Sarman Sibua; Zulhasmi Abasa; Risky Richlos Sarapung; Nurhani Mahmud; Ledy Yanti Lessy (JPM: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this activity is to increase awareness of clean living behaviors and create a healthy and independent environment as an effort to realize a health care village in achieving the SDGs. This activity is motivated by community problems, namely the low knowledge and awareness of clean and healthy living behaviors in Tanjung Saleh Village and Sakita Village. In fact, there are still many residents who dispose of garbage not at one shelter location, lack of environmental cleanliness, and there is garbage disposal on the coasts. The two villages have also never been touched by the socialization program of higher education thridharma in Morotai Island Regency. Thus, the community service team of the Faculty of Dentistry and Education, University of the Pacific, Morotai carried out community service activities and socialization to increase awareness of clean and healthy living behaviors. The service method uses a participatory approach that involves all teams and partners, namely the Tanjung Saleh and Sakita village communities to jointly discuss, provide solutions to problems, and find concrete solutions to overcome environmental hygiene problems. The stages of this service activity have been carried out by conducting a survey of the location of service, team preparation and consumption needs while in the village. Socialization activities about clean and healthy living behaviors to the community have been carried out with a participatory approach involving all teams and partners, namely the people of Tanjung Saleh and Sakita villages. In general, this service activity ran smoothly, which can be measured from the results of the training evaluation, there was a significant increase in the understanding of villagers. The average pretest score before training was 35, while the average posttest score after training increased to 95. So that the output of this service activity is fulfilled, which means that there is an increase in residents' awareness and knowledge of environmental problems. Another output is the production of articles on Worship to the Community.